Global Religious Institutions’ Responses to the Gaza Crisis: Solidarity, Tensions, and Pathways to Interfaith Peace - Andriansyah, Yuli (Millah: Journal of Religious Studies, 2025)
The escalation of the Israel-Palestine conflict since October 2023 has prompted extensive responses from religious institutions worldwide, illuminating the complex intersection of faith, ethics, and geopolitics in confronting humanitarian crises. This editorial examines these reactions to argue that, despite fostering widespread empathy and moral advocacy, their overall impact remains constrained by doctrinal divisions, internal polarizations, and geopolitical obstacles, necessitating enhanced interfaith coordination for meaningful change. The analysis draws on a synthesis of scholarly literature, institutional statements, and citation analyses from theological, peace studies, and international relations sources, focusing on key responses during 2024 while incorporating historical context and comparative regional perspectives. Christian institutions, led by the Vatican and Pope Francis, issued repeated calls for immediate ceasefires, emphasizing civilian protection and human dignity while navigating tensions in Catholic-Jewish relations amid debates over historical interpretations and universal brotherhood. The World Council of Churches advanced ecumenical resolutions urging divestment and solidarity with Palestinians, though contrasting views persisted between progressive humanitarian emphases and conservative support for Israel’s security claims. Islamic organizations, including the Organization of Islamic Cooperation and the Muslim World League, condemned Israeli actions through fatwas and resolutions framing solidarity as a humanitarian imperative, yet struggled with gaps between rhetoric and enforceable actions. Nahdlatul Ulama in Indonesia exemplified adaptive jurisprudence via “fiqh of civilization,” promoting moderate Islam, aid mobilization, and dialogue. Progressive Jewish voices critiqued policies through justice-oriented campaigns, challenging monolithic narratives, while non-Abrahamic traditions contributed nonviolence-based perspectives emphasizing shared suffering and decolonial frames. These diverse engagements highlight religion’s capacity to amplify calls for justice and humanitarian relief, yet reveal persistent challenges such as sectarian rifts, misinformation in digital spaces, and limited translation of statements into policy shifts or unified pressure. Regional contrasts, particularly Indonesia’s robust mobilization versus more neutral stances in parts of Asia, underscore demographic and historical influences on solidarity intensity. Ultimately, the editorial concludes that religious responses signal potential for stronger interfaith alliances and peace pathways, provided institutions prioritize concrete coordination, ethical charters, and anti-misinformation efforts. By bridging divides through shared values of compassion and dignity, faith communities can evolve from symbolic solidarity toward transformative contributions to Palestinian self-determination and regional stability.